Comparison of several Li doped scintillators for measurement of neutron and γ radiation integral quantities. (June 2022) - Tichý, Miloš; Huml, Ondřej
Abstract: Five types of scintillators for parallel detection of neutrons and γ were tested for their pulse shape discrimination ability. All detectors are based on 6 Li (n, alpha) 3 H reaction. LiI, ZnS and polystyrene were used as scintillators. Tests were performed at different neutron and γ mixed fields (AmBe, Cf) using a small Hamamatsu photomultiplier and a Picoscope digitizer. A polystyrene-based ZnS + LiF detector was proven to be the most suitable for neutron-γ separation and similar sensitivity for both types of radiation to construct a single device to measure integral quantities neutrons and γ (fluence, ambient dose equivalent) in parallel. The ZnS + LiF detector based on plexiglass, is in principle useable also, but has low sensitivity to γ radiation. The tested Li glass or LiI crystal does not have the ability to separate neutron and γ. With amplitude discrimination it can be used as a neutron detector for a much simpler probe for a Bonner spectrometer. Highlights: Pulse shape discrimination of neutrons and γ can be performed with affordable digitizer. A polystyrene-based ZnS + LiF detector is the most suitable for neutron-γ separation and sensitivity for both types of radiation. Measurement of (fluence, ambient dose equivalent of neutrons and γ in parallel is possible -based ZnS + LiF detector. Used Li glass or LiI crystal does not have the ability to separate neutron-γ.